Electrode Montage for Bilateral Cervical Vestibular-Evoked Myogenic Potential Testing. - Patterson, Jessie N.; El Hidek, Nour; Janky, Kristen L. (Journal of the American Academy of Audiology, 2024)
Background Cervical vestibular-evoked myogenic potentials (cVEMPs) are predominantly ipsilateral, myogenic responses originating from saccular activation. Some individuals have contralateral-crossed cVEMP responses with monaural air-conducted stimulation (ACS) which can contaminate cVEMP responses with bilateral stimulation. While the origin of the contralateral-crossed response is under debate, its presence has implications for cVEMP testing with midline bone conduction vibration (BCV). Purpose The purpose of this study was to determine the origin of the contralateral-crossed cVEMP response. It was hypothesized that the crossed response is due to electrode contamination and would disappear with a modified electrode montage. Research Design This is a cross-sectional research study. Study Sample Fifteen healthy participants (30 ears; mean age: 27.4 19–39; 10 females). Data Collection and Analysis Participants completed cVEMP testing using three stimulation methods (monoaural ACS, binaural ACS, and midline BCV) and two electrode montages (sternum reference and Fp reference). Results In the monoaural ACS with sternum reference condition, 53.3% ears had contralateral-crossed cVEMP responses that were in-phase with the ipsilateral response for all but three ears. Whereas in the monoaural ACS with Fp reference condition, 3% had a contralateral-crossed cVEMP response. ACS and BCV cVEMP corrected amplitudes were significantly larger in the sternum reference conditions, which is attributed to artificial enhancement from the in-phase contralateral-crossed responses. Conclusions The significant reduction of contralateral-crossed responses in the Fp reference condition suggests that the contralateral-crossed cVEMP response is due to reference electrode contamination and may be a more appropriate reference placement when completing cVEMPs with midline BCV.